Calls distinguish species of Antbirds (Aves: Passeriformes: Thamnophilidae) in the genus Pyriglena - Isler, Morton L.; Maldonado-Coelho, Marcos (Zootaxa, 2017)
Populations in the genus Pyriglena Cabanis, 1847, commonly known as fire-eyes, are patchily distributed in central South America from the Pacific slope of the Andes to the Atlantic Forest of Brazil. Pyriglena populations are currently placed into 12 taxa, only five of which are not isolated from their neighbors by distance, a high mountain range, or a major river. In the Thamnophilidae, taxonomic decisions regarding such allopatric populations have primarily rested on differences in vocalizations, thought not to be learned and to play a key role in the speciation process. When we examined Pyriglena vocalizations in this context, the outcomes revealed substantial diversity in their calls, rather than their songs. They commonly delivered four different types of calls, unusual although not unprecedented in thamnophilids. Diversity in calls rather than songs underscores the need to consider all vocalizations in taxonomic studies. The outcomes support the continued recognition of the White-shouldered Fire-eye Pyriglena leucoptera (Vieillot) and Fringe-backed Fire-eye Pyriglena atra (Swainson) as distinct species, and indicate that, in addition, the currently constituted Pyriglena leuconota should be considered three species: the Western Fire-eye Pyriglena maura (Ménétries); the Tapajos Fire-eye Pyriglena similis Zimmer; and the East Amazonian Fire-eye Pyriglena leuconota (von Spix). We also identify taxonomic uncertainties regarding subspecies that require acquisition of additional data and further analysis.